2017
DOI: 10.3892/or.2017.6027
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-induced cell migration in pancreatic carcinoma cells is RAC1 and NOX4-dependent and requires RAC1 and NOX4-dependent activation of p38�MAPK

Abstract: Transforming growth factor (TGF)-β promotes epithelial-mesenchymal transition and cell invasion of cancer cells in part through the small GTPase RAC1. Since RAC1 can signal through reactive oxygen species (ROS), we probed the role of the ROS-producing NADPH oxidase (NOX) and p38 mitogen-activated protein kinase (MAPK) in mediating TGF-β1/RAC1-driven random cell migration (chemokinesis). Although the NOX isoforms NOX2, 4, 5, 6, and RAC1 were readily detectable by RT-PCR in pancreatic ductal adenocarcinoma (PDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Other signaling molecules, including p38 mitogen-activated protein (MAP) kinase, focal adhesion kinase, and Src, are activated by VEGF-A and contribute to angiogenesis in endothelial cells [ 17 , 18 , 19 ]. The regulation and function of these signaling pathways are directly or indirectly associated with small G proteins [ 20 , 21 , 22 , 23 ].…”
Section: Relationship Between Vegf-a–vegf Receptor-2 Signaling Andmentioning
confidence: 99%
“…Other signaling molecules, including p38 mitogen-activated protein (MAP) kinase, focal adhesion kinase, and Src, are activated by VEGF-A and contribute to angiogenesis in endothelial cells [ 17 , 18 , 19 ]. The regulation and function of these signaling pathways are directly or indirectly associated with small G proteins [ 20 , 21 , 22 , 23 ].…”
Section: Relationship Between Vegf-a–vegf Receptor-2 Signaling Andmentioning
confidence: 99%
“…TGF-β1 plays a key role in the control of metastatic capacity of many malignancies [30,36].To demostrate the function of TGF-β1 on NPC cells,5-8F and HONE1 cells were cultured in 10% FBS medium with 0ng/ml,1ng/ml,5ng/ml,10 ng/ml of TGF-β1,respectively.After 48h,Scratch,Treanswell and Boyden asasay was used to detect the change in ability of migration and invasion( Figure.2A,B, C,D,E,F).As for 5-8F and HONE1 cells,metastatic capacity was enhanced in a concentration-dependent behavior.But,the diference between the experimental groups and the control group(0ng/ml TGF-β1 group) was statistical significance when the concentration of TGF-β1 was≥5ng/μl.And Western Blot was used to prove the change of EMT transformation,we found that the expression of E-cadherin was reduced,whereas,N-cadherin and VIMENTIN was increased( Figure.3 A,B).The results showed,compared to 0ng/ml TGF-β1,5ng/ml or 10ng/ml TGF-β1 promoted migration,invasion and EMT in NPC cells,and we gave that appropriate stimulus concentration of TGF-β1 was 5ng/μl.…”
Section: Tgf-β1 Induces Metastasis Of Npc Cellsmentioning
confidence: 99%
“…Especially in the terms of TGF-β1-induced EMT in malignant tumor cells [21 -23].The positive rates of TGF-β1 protein in NPC tissues obviously exceed that in nasopharyngeal inflammation tisses,and may correlate with NPC distant metastases [24][25].In fact,recent researches show TGF-β1 could participate in EMT of nasopharyngeal carcinoma cells [26][27][28][29].TGF-β1-induced migration requires RAC1-dependent activation of P38 in pancreatic carcinoma [30].Interesting,PTEN can inhibit Rac1 activity [10,31].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NOX4 may function as an antiapoptotic gene via another novel signaling pathway mediated by the state of JAK2 phosphorylation, which can be regulated by the production of ROS . During pancreatic cancer invasion, NOX4 induces the EMT mechanism and upregulates E‐cadherin to augment cell migration through the TGF‐β pathway, which has been correlated with the RAC/P38MAPK pathway.…”
Section: The Diverse Roles Of Nox4 In Cancersmentioning
confidence: 99%